2005
DOI: 10.4049/jimmunol.175.2.1197
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Induce Invasiveness of Epithelial Cancer Cells Via NF-κB and JNK

Abstract: Tumor-associated macrophages may influence tumor progression, angiogenesis and invasion. To investigate mechanisms by which macrophages interact with tumor cells, we developed an in vitro coculture model. Previously we reported that coculture enhanced invasiveness of the tumor cells in a TNF-α- and matrix metalloprotease-dependent manner. In this report, we studied intracellular signaling pathways and induction of inflammatory genes in malignant cells under the influence of macrophage coculture. We report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
314
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(337 citation statements)
references
References 48 publications
17
314
0
3
Order By: Relevance
“…Interestingly, it has been suggested that MIF may be particularly important in breast cancers with minimal nodal spread or with a node-negative phenotype and that MIF might play a role in tumor-stroma interactions of primary breast cancers (Bando et al, 2002). In support of such a notion, Hagemann et al (2005) have additionally implicated MIF in macrophageinduced invasiveness of epithelial breast cancer cells . These findings certainly justify future exploration in the context of our current results, bearing in mind, that the activation/blockade by MIF of other, Akt-independent apoptosis/survival-regulating pathways cannot be fully ruled out at the present time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been suggested that MIF may be particularly important in breast cancers with minimal nodal spread or with a node-negative phenotype and that MIF might play a role in tumor-stroma interactions of primary breast cancers (Bando et al, 2002). In support of such a notion, Hagemann et al (2005) have additionally implicated MIF in macrophageinduced invasiveness of epithelial breast cancer cells . These findings certainly justify future exploration in the context of our current results, bearing in mind, that the activation/blockade by MIF of other, Akt-independent apoptosis/survival-regulating pathways cannot be fully ruled out at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this system constituted a relevant cancer cell model, as MIF is strongly overexpressed in breast cancer and has been suggested to be associated with breast cancer development (Bando et al, 2002;Hagemann et al, 2005). Our results indicate that enhancement by MIF of Akt phosphorylation and survival is most marked in PTENand p53-negative breast cancer cells, whereas PTEN-and p53-positive breast cancer cells are unresponsive to exogenous MIF with respect to Akt activation and only seem to depend on MIF regarding their survival to a minor extent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the "mutant" u 2 cell population moves only in a directed manner (hence exhibiting an heterogeneous type of invasion) in response to cell-cell and cell-matrix adhesion forces. Biologically, this directed movement of "mutant" (more invasive) cancer cells can be explained by the increase of macrophage density near highly mutated cancer cells (Lin et al, 2006), which promotes the directed movement and invasion of these cancer cells, and decreases their random movement (Goswami et al, 2005;Hagemann et al, 2005). Therefore, in this study we assume that the movement of u 2 population due to random walk can be considered negligible.…”
Section: Derivation Of the Modelmentioning
confidence: 99%
“…However, in contrast to these previous models which are of parabolic type, here we consider a parabolic-hyperbolic model. More precisely, we assume that one "normal" cancer cell population moves both randomly and in a directed manner in response to cell-cell and cell-matrix adhesive forces, while a second "mutant" cancer cell population (i.e., a mutated clone) moves predominantly in a directed manner following cell-cell interactions (with cells from both populations) and cell-matrix interactions (as suggested by experimental observations in Goswami et al (2005); Hagemann et al (2005)). By incorporating this assumption, we aim to bring a more realistic approach to the models since the various intra-tumour cell sub-populations have been shown to be distinct not only in their adhesion capabilities but also in their motility and metastatic potential (Marusyk & Polyak, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MIF is overexpressed in numerous cancers, has been linked to the development of colon cancer, and has been proposed to constitute a molecular link between inflammation and cancer [5][6][7]. In a recent report, Hagemann et al conclude that tumor necrosis factor-a (TNF-a) induces tumour-associated macrophages to secrete MIF, which serves to enhance the invasive capacity of the tumour cells [8]. In line with these observations, MIF was found to promote the migration of hepatic carcinoma cells through the angiogenic factors interleukin-8 (IL-8) and vascular endothelial growth factor (VEGF) [9] and to stimulate the migration of microvascular endothelial cells [10].…”
Section: Introductionmentioning
confidence: 99%